ALGORITHM VISUALIZER - Reshma K. Malgonde; Rohit S. Koli; Shivprasad N. Waghmare (International Journal of Innovations in Engineering Research and Technology, 2022)
Algorithms are hard to understand for information technology/computer science students becausethey dynamically modify values of elements of ABSTRACT data structures. In this project sequence ofexecution of algorithms is explained visually. It helps to realize the fundamental concepts of algorithms such as searching and sorting method in simple manner. Animations can help to understand algorithms, since they connect ABSTRACT concepts to real life objects and situations Algorithm Visualizer illustrates how algorithms works. It mainly aims to simplify and deepen the understanding of algorithms operation. Within the paper we discuss the possibility of enriching the standard methods of teaching algorithms, with the algorithm visualizations. As a step in this direction, we introduce the Algorithm visualizer platform, present our practical experiences and describe possible future directions, based on our experiences.